Performance analysis comparison between non mixed-criticality and mixed-criticality system in microcontroller - Siti Nurhafizza Maidin; Noor Azurati Ahmad; Kamilia Kamardin; Shamsul Sahibuddin; Syahrizal Fadhlie Sabri (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Nowadays, implementation of real-time embedded system or safety-critical in a real-time system is significant within emerging technologies because the system involves many aspects such as safety and task execution without missing deadlines. The main cause of implementation is to avoid catastrophic loss. Besides that, effectuation of the mixed-criticality system in embedded system making system more complex for task execution. For an embedded system, the main component involves real-time scheduling. The implementation of DPM method in real-time scheduling is well known, but in the mixed-criticality system, DPM method is still lacking. In order to cater this problem, Dynamic Power management (DPM) method is deployed onto the microcontroller of the mixed-criticality system to save energy when executing tasks in order to have better performance in the system. The usage of the DPM method in mixed-criticality of microcontroller resulting decrease of 0.82% in LED output voltage value meanwhile, for the LCD output, the voltage value decreased by 1.37% in the home alarm system. Thus, the energy-saving in the microcontroller of the mixed-criticality system using the DPM method is defined.